When borne across : literary cosmopolitics in the contemporary Indian novel - Ghosh, Bishnupriya (Rutgers University Press, 2004)
Annotation India's 1997 celebration of the Golden Jubilee marked fifty years of independence from British colonial rule. This anniversary is the impetus for Bishnupriya Ghosh's exploration of the English language icons of South Asian post-colonial literature: Salman Rushdie, Vikram Chandra, Amitav Ghosh, Upamanyu Chatterjee, and Arundhati Roy. These authors, grouped together as South Asian cosmopolitical writers, produce work challenging and expanding preconceived notions of Indian cultural identity, while being sold simultaneously as popular English literature within the global market. This commodification of Indian language and identity reinforces incomplete and simplified images of India and its writers, and at times counteracts the expressed agenda of the writers. In When Borne Across, Ghosh focuses on the politics of language and history, and the related processes of translation and migration within the global network. In so doing, she develops a new approach to literary studies that adapts conventional literary analysis to the pressures, constraints, and liberties of our present era of globalization
Keywords: Indic fiction (English) -- History and criticism.; Politics and literature -- India.; Cosmopolitanism -- India.; Roman de l'Inde (anglais) -- Histoire et critique.; Politique et littérature -- Inde.; Cosmopolitisme -- Inde.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Cosmopolitanism; Indic fiction (English); Politics and literature; India; Litteratur -- Engelsk, amerikansk litteratur.; Criticism, interpretation, etc.